Source localization of tone perception in alcoholic brain indexed by standardized low-resolution electromagnetic tomography - Vachrintr Sirisapsombat; Phakkharawat Sittiprapaporn; Chaiyavat Chaiyasut; Sasithorn Sirilun; Roungsan Chaisricharoen; Thamthiwat Nararatwanchai (Institute of Advanced Engineering and Science, 2020)
Alcohol consumption is known to associate with several diseases, injuries, and social problems. The long-term, excessive alcohol exposure can lead to liver cirrhosis and pancreatitis. After repating alcohol exposure, alcohol dependence would develop an individually behavioral, cognitive, and physiological phenomenon. Previous studies indicated that although the left hemisphere was selectively employed for processing linguistic information irrespectively of acoustic cues or subtype of phonological unit, the right hemisphere was employed for prosody-specific cues. These previous studies provided the impetus for future investigations of tone perception and temporal integration differences in tonal brain speaker who had long-term, excessive alcohol exposure such as Thai in the present study. The present study used both an auditory mismatch negativity (MMN) component of event-related potentials (ERPs) recording and the standardized Low-resolution Electromagnetic Tomography (sLORETA) techniques to measure the degree of cortical activation and to localize the brain area contributing to the scalp recorded auditory MMN component during the passive oddball paradigm. Ten healthy right-handed adults participated in this study. The findings showed that both [kha:] - mid tone perception and [khá:] - high tone perception elicited a strong MMN between 215-284 ms with reference to the standard-stimulus ERPs. Source localization was obtained in the middle temporal gyrus of the right hemisphere for both [kha:] - mid tone perception and [khá:] - high tone perception. Automatic detection of tone perception in alcoholic tonal brain is a useful index of language universal auditory memory traces.